2021
DOI: 10.3389/fgene.2021.628904
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of Phospholipase A2 Associated Neurodegeneration Phenotype Based on the Long-Term Follow-Up of a Large Hungarian Family

Abstract: IntroductionPhospholipase A2-associated Neurodegeneration (PLAN) is a group of neurodegenerative diseases associated with the alterations of PLA2G6. Some phenotype-genotype association are well known but there is no clear explanation why some cases can be classified into distinct subgroups, while others follow a continuous clinical spectrum.MethodsLong-term neurological, and psychiatric follow-up, neuropathological, radiological, and genetic examinations, were performed in three affected girls and their family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We found 7 references, and predefined data were extracted. The summary of the demographic, clinical, genetic, and radiological data of the reported 21 patients in literature ( Table 2 ) ( 4 , 5 , 14 18 ) was shown in Table 1 , where among the 21 ANAD patients, 86% (18/21) have iron deposition, 62% (13/21) parkinsonism, 71% (15/21) cerebellar atrophy, 67% (14/21) pyramidal signs, 52% (11/21) cognitive impairment, and 29% (6/21) nystagmus or Strabismus. Genetic analysis had been conducted on eleven of the reported ANAD patients, and c.238G>A was found to be the most popular mutation, which was detected in two unrelated pedigrees.…”
Section: Resultsmentioning
confidence: 99%
“…We found 7 references, and predefined data were extracted. The summary of the demographic, clinical, genetic, and radiological data of the reported 21 patients in literature ( Table 2 ) ( 4 , 5 , 14 18 ) was shown in Table 1 , where among the 21 ANAD patients, 86% (18/21) have iron deposition, 62% (13/21) parkinsonism, 71% (15/21) cerebellar atrophy, 67% (14/21) pyramidal signs, 52% (11/21) cognitive impairment, and 29% (6/21) nystagmus or Strabismus. Genetic analysis had been conducted on eleven of the reported ANAD patients, and c.238G>A was found to be the most popular mutation, which was detected in two unrelated pedigrees.…”
Section: Resultsmentioning
confidence: 99%
“… 6 Another study in 2021 presented a girl with bilateral optic nerve atrophy (without retinal hyperpigmentation). 7 An abnormal iron deposition follows a specific pattern of almost symmetrical involvement of the deep grey matter nuclei of the brain in NBIA. 8 Neurodegeneration with brain iron accumulation (NBIA) encompasses a group of inherited disorders that share the clinical features of an extrapyramidal movement disorder accompanied by varying degrees of intellectual disability and abnormal iron deposition in the basal ganglia (e.g., globuspallidus mainly).…”
Section: Discussionmentioning
confidence: 99%
“… 2 A case study from Hungary showed the development of severe spastic paraparesis with moderate ataxia in two girls diagnosed with PLAN. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation